Remote Auditing, Aspect of Auditor Behavioral and Use Of Technology - Zakir Gunibala; Ari Kurniawan Putra; Ayu Andini (UNIB Press, 2024)
This scoping review aims to map out existing studies related to remote auditing that focus on the topics of auditors' behavioural and technology use. The importance of auditors' adaptation to the challenges posed by the pandemic and the need for improved skills and knowledge in the face of a changing work environment. This review refers to five stages, namely: 1) identification of research questions; 2) identification of relevant research; 3) selection of articles; 4) data mapping; and 5) compiling, summarising and reporting the results. The time span of the article is 2021-2024. The results of this review revealed that most studies recognised an increase in the efficiency of their daily tasks in terms of remote auditing. However, there is still debate regarding auditor behaviour that is influenced by remote auditing activities, which is feared to reduce skepticism. In addition, the use of technology in remote auditing brings data security threats. Therefore, further research is needed to uncover auditor scepticism and data security in remote audit activities. This review is expected to provide greater insight into the importance of remote auditing, auditor adaptation to change, and technology utilisation in improving audit quality in today's digital era